Challenges Of Exchange Rate Fluctuation And Cpo Prices In Indonesia Palm Oil Industry - Achmad Daengs GS; Annisa Rahmawati; Maria Yovita R Pandin (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Objective : This study points to analyze the challenges of Rupiah Exchange Rates and International CPO Prices to Indonesia's CPO Export Volume. Design /methodology/approach : this research exercises explanatory type under a quantitative approach. Data collection techniques in this study were done by time series techniques. The data analysis technique used is Structural Equation Model (SEM) with the Smart Partial Least Square (PLS) tool. Findings : The study results indicate that: (1) Rupiah Exchange Rates do not have a significant effect on Indonesia's CPO Export Volume; (2) International CPO prices have a significant effect on Indonesia's CPO Export Volume. Practical implications : intensify business in economy sector in order to reach the lower class people. Paper type : research paper Keywords: Rupiah Exchange Rates, International CPO Prices, Export Volume